Resource descriptions, ontology, and resource discovery. (7th July 2010) - Lacroix, Zoe; Aziz, Maliha
Resource discovery systems may assist scientists in the selection of bioinformatics resources suitable to implement scientific workflows. In this paper we address several problems related to resource discovery. They include resource publication formats, resource registration, and syntactic vs. semantic discovery. We analyse the BioMoby registry and present an algorithm that curates the BioMoby hierarchy into an ontology for use in semantic-driven resource discovery.